2018
DOI: 10.1186/s41182-017-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of pathophysiological processes during murine experimental Schistosoma japonicum infection using high-resolution ultrasound imaging

Abstract: BackgroundHepatosplenic lesion formation is one of the typical clinical symptoms of schistosomiasis japonica. Although it is established that circum-oval granuloma formation mediated by T lymphocytes is the key event triggering the formation of hepatic lesions, the time-course kinetics of disease progression remains to be fully elucidated.MethodsThe real-time process of the pathophysiology of schistosomiasis japonica from the early to late clinical phase was non-invasively observed in a murine experimental inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…Mothers were asked whether the child under the age of five years had experienced symptoms of diarrhoea in the 2 weeks prior to the survey. In our study, the measurement of diarrhoea was specific to the child age group for each of the IYCF indicators, and this method was consistent with previously published studies [ 28 , 29 , 30 ].…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Mothers were asked whether the child under the age of five years had experienced symptoms of diarrhoea in the 2 weeks prior to the survey. In our study, the measurement of diarrhoea was specific to the child age group for each of the IYCF indicators, and this method was consistent with previously published studies [ 28 , 29 , 30 ].…”
Section: Methodssupporting
confidence: 86%
“…The exposure variables were the IYCF indicators, defined in accordance with the World Health Organisation (WHO) definition for assessing IYCF practices in populations [ 31 ]. These IYCF indicators were selected based on past studies from LMICs, which showed that these indicators were associated with diarrhoea [ 28 , 29 , 30 , 32 , 33 , 34 ]. EIBF or timely initiation of breastfeeding was defined as the proportion of children within 0–23 months of age who were breastfed within one hour of birth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the initial interaction of the egg with the immune system–when it is deposited in the blood stream–will not be accessible by this system. High-resolution ultrasonography has been recently shown to be applicable for noninvasive time-course observations of hepatic lesions in S. japonicum infection in mice ( 172 ). Furthermore, the development of other noninvasive techniques, such as small-animal PET-MRI or intravital 2-photon microscopy may be helpful tools to study early events of granuloma formation, as undertaken in the liver ( 173 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has been made in the reduction of global diarrheal deaths, there is still much work to be done [ 6 , 7 ]. The World Health Organization (WHO) estimates show that there are significant geographic variations in the global burden of foodborne illnesses given mortality estimates across sub-regions [ 8 ]. Africa experienced the highest burden per population, followed by South East Asia and Eastern Mediterranean, primarily due to inadequate food safety knowledge [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%